Efek Antipiretik Kombinasi Ekstrak Daun Cocor Bebek (Kalanchoe pinnata L.) Dan Ekstrak Daun Tembelekan (Lantana camara L.) Pers. Terhadap Marmut (Cavia porcellus) Dengan Demam Yang Diinduksi Pepton: Antipyretic Effect of Extract Combination of Cocor Bebek (Kalanchoe pinnata L.) Leaves And Tembelekan (Lantana camara L.) Pers. Leaves on Guinea Pigs (Cavia porcellus) With Peptone Induced Fever - Heni Purwitasari; Yuliet Yuliet; Ihwan Ihwan (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2017)
Cocor Bebek (Kalanchoe pinnata L.) is a medicinal plant that has been used as traditional medicine for long period, used to fight fever, but it empirically leaves of Tembelekan (Lantana camara L.) are also generally primarily used to treat fever. Research on the effects of the combination of Cocor Bebek’s leaf extract (Kalanchoe pinnata L.) and the leaf extract of tembelekan (Lantana camara L.) Pers on male guinea pig (Cavia porcellus) is induced peptone 5% at a dose of 150 mg / kg body weight. With the aim to determine the effect of the combination and determine the effects of the most effective as an antipyretic. Extracts prepared by maceration method using ethanol 95%. Marmots were divided into 4 groups. Each guinea pig was induced using peptone 5%. The first group was given Na CMC as a negative control group 2nd given a combination of one dose combinations (50 + 720). Group 3 was given a second dose combination (100 + 720). Group-4 were given a 3-dose combination (150 + 720). Temperature measurement is carried out for 2 hours with a 30 minute interval. Data were analyzed temperature measurements were statistically analyzed using ANOVA (Analisys Of Variance). The research result was addressing, that the combination of extracts can reduce fever. The combination is most effective as an antipyretic is cocor duck leaf extract 50 mg and 720 mg tembelekan leaf extract (50 + 720).